Living in Artistic Career: The Role of Job Crafting towards Work Identity for Musicians - Widhawan Aryo Pradhita (Faculty of Psychology Universitas Gadjah Mada, 2022)
Professional musicians have been continuously facing difficulties in career over time. One of the psychological threats for musicians is to lose their identity at work, which may lead to abandonment of their potential lifetime career. Previous studies have not emphasized the importance of certain work efforts to maintain work identity in the context of music career. This study conducted a literature review on the job crafting role to musicians’ work identity, and aimed to elaborate the existing concepts with the context of music profession. Using theoretical frameworks of job crafting and Job Demand-Resource theory, this study proposed theoretical perspectives to support the theories, by identifying five dimensions of job crafting (task, relational, cognitive, emotional, and physical) for professional musicians, as well as building a conceptual model that may help musicians to maintain work identity. This study also contributed theoretical insights and implications regarding the job crafting role towards identity construction for musicians, which could be considered during the current pandemic.